Exploring personality traits in the knowledge-sharing behavior: the role of agreeableness and conscientiousness among Malaysian tertiary academics - Norazha, Paiman; Fauzi, Muhammad Ashraf; Natrika, Norizan; Aida, Abdul Rashid; Tan, Christine Nya-Ling; Wider, Walton; Ravesangar, Kamalesh; Selvam, Gowri (Emerald Publishing Limited, 2023)
Purpose: The research aims to provide a nuanced understanding of the complex social, psychological and organizational factors that serve as the foundation driving academics' knowledge-sharing behavior (KSB) within an academic enclave. Design/methodology/approach: A cross-sectional research design using the partial least squares structural equation modeling (PLS-SEM) approach was employed to examine the determinants of personality traits among tertiary academics in Malaysia in relation to their KSB. To this end, a self-administered survey was distributed to a sample group of 526 respondents. Findings: It is evident that conscientiousness and agreeableness are the personality traits that play a significant role in promoting KSB among academics in higher learning institutions (HLIs). These personality traits are positively linked with academics' willingness to transfer and receive knowledge. In contrast, the personality trait of openness to experience does not significantly influence KSB. Research limitations/implications: This study has employed a four-item measurement for evaluating the three distinct personality traits. Despite employing a brief measurement tool, the study has demonstrated significant reliability and validity, particularly in terms of convergent and discriminant validity. Practical implications: The present study has revealed that conscientiousness in academics is intimately linked with their KSB, which is of paramount importance in the output-based education system. Notably, agreeableness among academics also conveys a positive effect on knowledge sharing (KS) in HLIs, as it cultivates trust and helpfulness among individuals and facilitates the exchange of valuable tacit knowledge. Originality/value: This research explores the relationship between personality traits and KSB among Malaysian academics in HLIs. The study adopts the theories of planned behavior (TPB) and social capital theory (SCT) as theoretical ground, providing a nuanced understanding of the underlying motivations and mechanisms driving academics' knowledge-sharing behavior within the unique socio-cultural context of Southeast Asia.